Kekerasan Anak Pada Keluarga Buruh di Jepara Perspektif Pendidikan Islam - Ahmad Saefudin; Sofia Ridwana; Hayu Yulistianti (Universitas Negeri Medan, 2021)
Child abuse within the family sphere is often a hidden crime phenomenon because it is kept secret by both the perpetrator and the victim. This article seeks to uncover the practice of child abuse in labor families in Geneng, Jepara, identify the causes, and offer solutions. The data collection used interview, observation, and documentation. The key informants are children, parents who work as laborers, and the Head of Geneng Village. The collected data is then analyzed using descriptive qualitative research from the perspective of Islamic education theory. Doctrinaire, Islam never allows parents to behave rudely to children. Unfortunately, not a few of those who fail to understand and become perpetrators of child abuse. The forms are varied, ranging from psychological violence such as insults, insults, and shouting. The main causes are family economic poverty factors and poor understanding of parents' religion. The way out for parents who are busy working is to get their children in Madrasah Diniyah (Madin). No less important, after Maghrib, children are encouraged to take part in studies conducted by local religious teachers around their homes.